2005
DOI: 10.1007/s10750-004-4397-y
|View full text |Cite
|
Sign up to set email alerts
|

Oogenesis and oocytes

Abstract: The morphological features of polychaete ovarian morphology and oogenesis are reviewed. Some basic information on ovarian structure and/or oogenesis is known for slightly more than half of recognized polychaete families although comprehensive studies of oogenesis have been conducted on $0.1% of described species. Relative to other major metazoan groups, ovarian morphology is highly variable in the Polychaeta. While some species appear to lack a defined ovary, most have paired organs that are segmentally repeat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 58 publications
3
27
0
1
Order By: Relevance
“…The autoradiographic studies mentioned above also demonstrated active transcription and translation within the oocyte (Ruthmann, 1964;Emanuelsson, 1985;Emanuelsson and Anehus, 1985). In this respect, oogenesis in O. labronica is similar to that observed in other polychaetes, in which oocytes are typically transcriptionally active (Eckelbarger, 1992(Eckelbarger, , 2005(Eckelbarger, , 2007. This strategy differs markedly from that of insects with polytrophic ovarioles (i.e., those with nurse cells), in which oocyte nuclei have greatly reduced transcriptional activity, and lack nucleoli for much of the vitellogenic stage of oogenesis (King and Burnett, 1959;Mahowald and Tiefert, 1970).…”
Section: Synthetic Activity In Nurse Cells and Oocytessupporting
confidence: 58%
“…The autoradiographic studies mentioned above also demonstrated active transcription and translation within the oocyte (Ruthmann, 1964;Emanuelsson, 1985;Emanuelsson and Anehus, 1985). In this respect, oogenesis in O. labronica is similar to that observed in other polychaetes, in which oocytes are typically transcriptionally active (Eckelbarger, 1992(Eckelbarger, , 2005(Eckelbarger, , 2007. This strategy differs markedly from that of insects with polytrophic ovarioles (i.e., those with nurse cells), in which oocyte nuclei have greatly reduced transcriptional activity, and lack nucleoli for much of the vitellogenic stage of oogenesis (King and Burnett, 1959;Mahowald and Tiefert, 1970).…”
Section: Synthetic Activity In Nurse Cells and Oocytessupporting
confidence: 58%
“…The morphological features selected for assessing relationships at family level were scored from the literature (e.g. Dales, 1962; Orrhage, 1980; Bartolomaeus, 1995, 1998; Purschke, 1997, 2005; Hausen & Bartolomaeus, 1998; Rouse, 2000a, b; Zhadan & Tzetlin, 2003; Bartolomaeus & Quast, 2005; Eckelbarger, 2005; Hausen, 2005; Orrhage & Müller, 2005; Tzetlin & Filippova, 2005; Purschke & Müller, 2006; Purschke & Hausen, 2007; Suschenko & Purschke, 2009). The list of 99 characters and states is summarized in Table 2 and described in .…”
Section: Methodsmentioning
confidence: 99%
“…It is likely that these clusters are a germ plasm which is well known from primordial and early germ cells as well as from the embryos of many metazoans (Extavour and Akam 2003). The germ plasm has been described in many morphological embodiments including groups of dense particles associated with mitochondria (Eddy 1975; Wourms 1987; Eckelbarger 2005) identical to those observed in previtelllogenic oocytes of Ph. harmeri .…”
mentioning
confidence: 94%